2023
DOI: 10.3390/nano13152178
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Metal–Organic Frameworks for the Removal of Chemical Warfare Agents: Insights into Hydrolysis and Oxidation Reaction Mechanisms

Abstract: The destruction of chemical warfare agents (CWAs) is a crucial area of research due to the ongoing evolution of toxic chemicals. Metal–organic frameworks (MOFs), a class of porous crystalline solids, have emerged as promising materials for this purpose. Their remarkable porosity and large surface areas enable superior adsorption, reactivity, and catalytic abilities, making them ideal for capturing and decomposing target species. Moreover, the tunable networks of MOFs allow customization of their chemical funct… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 118 publications
0
0
0
Order By: Relevance
“…This is consistent with a type V isotherm under the IUPAC classification. It was further argued that this type V behavior would be more advantageous than strongly hydrophilic (Type I) or hydrophobic (type III) behavior . In light of our results, the indications that uptake increased with RH is very interesting.…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…This is consistent with a type V isotherm under the IUPAC classification. It was further argued that this type V behavior would be more advantageous than strongly hydrophilic (Type I) or hydrophobic (type III) behavior . In light of our results, the indications that uptake increased with RH is very interesting.…”
Section: Resultssupporting
confidence: 79%
“…Accordingly, an earlier study showed that solid-phase hydrolysis rates are much lower than those in buffer solutions and that raising the water content of NU-1000 from 0 to 400% only slightly increased the hydrolysis rate of the simulant dimethyl 4-nitrophenyl phosphate . Several recent reviews have highlighted the importance of both water and a suitable base in solid-state hydrolysis; ,, even if an OP-agent effectively binds to a hydrated Zr-node and HF is eliminated after nucleophilic attack, a base may still be important for removal of the hydrolysis product. Further, if the hydrolysis product has a high binding energy, the hydrolytic reaction may become stoichiometric rather than catalytic .…”
Section: Resultsmentioning
confidence: 99%